Irreducible Plurality, Indivisible Unity: Singapore Relational Constitutionalism and Cultivating Harmony Through Constructing a Constitutional Civil Religion. Issue 7 (October 2019) - Thio, Li-ann
Abstract: This Article seeks to explore the nature, function, source, and content of a constitutional civil religion (CCR) within Singapore's constitutional experiment in managing the diversity of race and religion and promoting solidarity. CCR is constructed as a strategy to secure social harmony within the world's most religiously diverse polity, through recognizing an irreducible plurality in ethnic and religious terms, while maintaining an indivisible unity through nurturing bonds of citizen solidarity. This dovetails with the function of the constitution as an instrument of social integration, involving the articulation and regular affirmation of shared community values and aspirations, as well as process and practices—or public rituals—which regulate dispute resolution or conflict management during instances or crises where racial and religious harmony is threatened. A functional approach is taken towards the idea of a civil religion, and the tasks of integration, legitimation, and inspiration it may play within a constitutional order. The nature of civil religion in general, and the sources of CCR in Singapore, as well as its expression as a public ritual in managing religious disharmony disputes is discussed.